Expressive inferences & mighty obstacles - Soria-Ruiz, Andrés (Proceedings of the Amsterdam Colloquium, 2024)
Predicates of personal taste (PPTs, i.e. tasty) carry so-called acquaintance inferences (AI), to the effect that the speaker has first-hand experience. In addition, Willer and Kennedy (2020) have observed a parallel phenomenon in the moral domain: moral predicates (MPs, i.e. okay) carry what they call practical inferences (PI), to the effect that the speaker has a practical stance towards whatever they are judging. My purpose is two-fold. First, whereas extant accounts have characterize modals and other operators as obviating AI/PI, the right generalization is stronger, namely that these inferences "flip" in those environments. Secondly, available theories provide either a principled account of AI that can hardly be extended to PI (Anand and Korotkova 2018; Ninan 2024), or a uniform but unexplanatory account of both inferences (Willer and Kennedy 2020). I propose a minimal amendment of Ninan 2024 so that it can be extended to PI in a principled way.